1993
DOI: 10.1093/clinids/17.supplement_1.s117
|View full text |Cite
|
Sign up to set email alerts
|

New Prospective Studies of the Association of Ureaplasma urealyticum Colonization and Chronic Lung Disease

Abstract: This study examined the association between Ureaplasma urealyticum colonization and the development of chronic lung disease (CLD) in 93 premature infants who were treated with surfactant and who had birth weights < 1251 g. Nasopharyngeal and tracheal cultures for U. urealyticum were obtained at 2 +/- 1 and at 14 +/- 1 days after birth and were positive in 17 (18%) of 93 patients. Infants born vaginally were 4.5 times more likely to be colonized than were those born by cesarean section. Colonization with U. ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
25
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 10 publications
10
25
0
1
Order By: Relevance
“…This is in agreement with the percentage of colonization of U. urealyticum in neonatal respiratory specimens reported in other studies from 3 to 23% (Blanchard et al, 1993;van Waarde et al, 1997;Payne et al, 1993;Jonsson et al, 1994;Mohagheghi et al, 2013). Higher rates were reported by Nelson et al (1998) (2000) (55%) that could be explained by larger sample size, or testing multiple specimens from enrolled patients.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the percentage of colonization of U. urealyticum in neonatal respiratory specimens reported in other studies from 3 to 23% (Blanchard et al, 1993;van Waarde et al, 1997;Payne et al, 1993;Jonsson et al, 1994;Mohagheghi et al, 2013). Higher rates were reported by Nelson et al (1998) (2000) (55%) that could be explained by larger sample size, or testing multiple specimens from enrolled patients.…”
Section: Discussionsupporting
confidence: 90%
“…This correlates with previous clinical studies that independently link Ureaplasma with BPD (19 -22) and death (22) despite surfactant treatment (21), and more recent studies and reviews continue to support this link (23)(24)(25). These studies showed differences in the studied populations, entrance criteria, and study design.…”
Section: Discussionsupporting
confidence: 86%
“…Although this work demonstrates a strong associ- (14) 0 (0) 14 (17) . in magnitude to that obtained in the univariate analysis.…”
Section: Discussionmentioning
confidence: 63%